High spectral and spatial resolved encryption and decryption of 3D color object based on holographic imaging spectroscopy. (October 2021) - Lin, Chao; Han, Yanli; Lou, Shuli; Li, Zengyan
Highlights: A 3D color object is encrypted based on holographic imaging spectroscopy in a single registration process to increase efficiency. Multiple dimensional of keys including complex amplitude, distance and spectrum is achieved in optical cryptosystem to enhance security. A noise free recovery of original 3D color object is demonstrated based on the decrypted images at multiple-wavelength to improve integrity. Abstract: We propose a new method to secure 3D color object using the holographic imaging spectroscopy technique. First, the original 3D color object is illuminated with a super-continuum white laser source with no necessity to decompose 3D color object into RGB components in advance which is commonly a preprocessing operation in traditional monochromatic illuminated optical cryptosystem. The output spectrum of white laser can be used as an additional key. Then, we design an optical cryptosystem based on hyperspectral holography in order to encrypt both the spectral and spatial information simultaneously with a high spectral-spatial resolution. Finally, the decrypted images at multiple-wavelength are numerically averaged to significantly reduce the speckle noise which is hard to be eliminated in optical cryptosystems with monochromatic illumination. The feasibility of our proposal is validated with experimental hyperspectral images and numerical simulation.